Publications Received (Academy of Management Review, 1989)
The article presents a list of books related to management. They include “A fighting Chance: New Strategies to Save Jobs and Reduce Costs,” by Sally Klingel and Ann Martin, “Bottom-Up Marketing,” by Al Ries and Jack Trout, and “Abilene Paradox: and Other Meditations on Management,” by Jerry B. Harvey.